Green Accounting and Material Flow Cost Accounting as Determinants of Sustainable Development: Evidence from Indonesian Mining Companies - Sofi Apriyanti; Dewi Kusumowati; Wahyu Setiyorini (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the effect of Green Accounting and Material Flow Cost Accounting on Sustainable Development in mining companies listed on the Indonesia Stock Exchange from 2022-2024. The population used in this study was 63 mining companies listed on the Indonesia Stock Exchange. Based on sample selection using purposive sampling, 15 company samples were obtained with 3 research periods, resulting in a total of 45 samples. This research method uses a quantitative approach with multiple linear regression analysis using software SPSS. This study uses secondary data in the form of financial reports and sustainability reports of companies. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that Green Accounting has a positive effect on Sustainable Development, indicating that improvements in environmental cost management and disclosure contribute to improvements in corporate sustainability performance. Material Flow Cost Accounting has a positive effect on Sustainable Development, and is even the most dominant variable in explaining variations in Sustainable Development because it promotes resource efficiency and waste reduction in the production process. Simultaneously, Green Accounting and Material Flow Cost Accounting are proven to have a significant effect on Sustainable Development with a high coefficient of determination, so that the model is considered capable of explaining most of the sustainability variation in the mining companies studied. Research implication is that green accounting significantly promotes sustainable development through improved transparency and environmental accountability, while material flow cost accounting contributes to sustainability mainly when integrated into broader strategic and environmental management practices.